BABAD PASEK DUKUH SEBUN: ANALISIS STRUKTUR DAN FUNGSI - Edy Hermayasa, Putu (Humanis; Volume 11. No2. Mei 2015)
This study examine the text of thechronicle Pasek Dukuh Sebun with the aim of helfing to foster, preserve, and develop traditional works (chronicle). Theory used is the theory of the sturcture and function theory. Structure theory is a theory os the srtucture used by Teeuw in his book "introduction to the science literature and the theory of function developed by S.O Robson. To simplify the analysis used method consists of several stage, namely : 1) the stage of providing data by using methods and techniques rever to techniques used are the recording and assisted with translation techniques: 2) stages of data analysis using qualitative methods and techniques used are descriptive analytic techniques; 3) stage of data analysis using informal methods and techniques used are inductive dedutive techniques. The results of this research is to build a structure unfolding chronicle text Pasek Dukuh Sebun good farm, content, of functions containded therein. From in this study include the type and variety of language contents include flow, incident, character and characterization, seting: the element and the element of tmie, theme, and mandate. Function include historical, religious function, and sosial fuction
Keywords: Chronicle, structure, function